Politico-Pedagogical Functions of Humour in South Asia - Kumar, Ravi; Paul, Rama (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
Humour as a performance has been studied at length from the prism of its relationship to politics. However, there are fewer works that looks at humour as pedagogy. Pedagogy includes every aspect of an individual as embedded in a socio-economic and political order. This embeddedness brings an individual face to face with diverse sources from which it learns. The paper argues that humour in its different avatars fulfils the purpose of teaching-learning in the same way as any other pedagogical tool. By acting as such it ensures its role as working for the status quo as well as for the anti-status quoists. Humour then ceases to be a mundane experience without any relevance but becomes one of the most sources of consensualisation as well as rebellion in contemporary times.